A new species group in the genus Dichaetophora, with descriptions of six new species from the Oriental region (Diptera, Drosophilidae) - Yang, J.H.; Toda, M.J.; Suwito, A.; Hashim, Rosli; Gao, J.J. (Pensoft Publishers, 2017)
The genus Dichaetophora Duda comprises 61 described species classified into four species groups: agbo, tenuicauda, acutissima and sinensis. This genus is distributed exclusively in the Old World, and is rich in species in the tropical and subtropical areas of the Oriental, Australasian, and Afrotropical regions. In this paper, a new species group, the trilobita group, is established for six new species discovered from the Oriental region. The delimitation of these species is firstly performed in light of morphology and further with the aid of DNA sequences of the mitochondrial COI and COII (cytochrome c oxydase, subunits I and II, respectively) genes, considering also their respective geographical origins. Then, the new species (trilobita Yang & Gao, sp. n., heterochroma Yang & Gao, sp. n., flatosternata Yang & Gao, sp. n., borneoensis Yang & Gao, sp. n., javaensis Yang & Gao, sp. n., and sumatraensis Yang & Gao, sp. n.) are described, and a key, based on not only morphological but also molecular information, is provided.